Identification of Myxobolus episquamalis (Myxozoa, Myxobolidae) in flathead mullet Mugil cephalus (Pisces, Teleostei, Mugilidae) from the coast of Senegal (eastern tropical Atlantic ocean) - Diamanka, Arfang (Array, 2008)
Myxobolus episquamalis (Myxozoa, Myxobolidae), mikrosporidijski nametnik, pronađen je po prvi put u cipla glavaša (Mugil cephalus) u senegalskom priobalju